What determines demand for digital community currencies? OurVillage in Cameroon - Jennifer Pédussel Wu; Martina Metzger; Ignacio Silva Neira; Arafet Farroukh (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2023)
Community currency systems are now turning to digital methods to increase the social outreach of member households in remote areas, mitigate detrimental effects in times of crises, and promote community social cohesion. The resilience of digital community currency systems depends on a set of decisive factors including stability, sustainability, and technical functionality. OurVillage in Cameroon is a socio-economic project that aims to increase and promote economic activity through the introduction of a blockchain-based local community currency system. This paper explores the potential of electronic complimentary payment systems by examining the underlying motivations for consumer use based on their socio-economics characteristics. We develop a demand estimate for the community currency, concentrating on the underlying environmental conditions of the target population. A demand study is helpful in order to observe the optimal conditions for goods' consumption, in this case the community currency system. The resulting estimation provides fundamental insights into the quality of the project and the determinants for successful implementation. Our findings have important policy implications, particularly for communities intending to introduce their own digital community currency systems.
Keywords: B4; C10; D02; E42; O12; 330; demand estimates; community currency; socio-economic development projects